Validity and reproducibility of the PERSIAN Cohort food frequency questionnaire: assessment of major dietary patterns - Sareh Eghtesad; Sahar Masoudi; Maryam Sharafkhah; Bahram Rashidkhani; Ali Esmaeili-Nadimi; Farid Najafi; Elnaz Faramarzi; Reza Homayounfar; Pedram Ebrahimnejad; Alireza Ansari-Moghaddam; Mohammadreza Mirjalili; Hossein Poustchi; et al. (Nutrition Journal, 2024)
Abstract Background Dietary patterns, encompassing an overall view of individuals’ dietary intake, are suggested as a suitable means of assessing nutrition’s role in chronic disease development. The aim of this study was to evaluate the validity and reproducibility of a food frequency questionnaire (FFQ) designed for use in the Prospective Epidemiological Research Studies in IrAN (PERSIAN), by comparing major dietary patterns assessed by the FFQ with a reference method. Methods Study participants included men and women who enrolled in the PERSIAN Cohort Study at seven of the eighteen centers. These centers were chosen to include dietary variations observed among the different Iranian ethnic populations. Two FFQ were completed for each participant over a one-year study period (FFQ1 upon enrollment and FFQ2 at the end of the study), with 24 interviewer-administered 24-hour dietary recalls (24 h) being completed monthly in between. Spearman correlation coefficients (SCC) were used comparing FFQs 1 and 2 to the 24 h to assess validity, while FFQ1 was compared to FFQ2 to assess reproducibility of the questionnaire. Results Three major dietary patterns—Healthy, Low Protein/High Carb and Unhealthy—were identified, accounting for 70% of variance in the study population. Corrected SCC ranged from 0.31 to 0.61 in the validity and from 0.34 to 0.57 in reproducibility analyses, with the first two patterns, which accounted for over 50% of population variance, correlated at above 0.5 in both parameters, showing acceptable findings. Conclusions The PERSIAN Cohort FFQ is suitable for identification of major dietary patterns in the populations it is used for, in order to assess diet-disease relationships.